"Itsári", roots, raízes: um estudo de caso sobre o disco Roots da banda Sepultura - Flávio Garcia da Silva (2019)
This work aims to promote a discussion about cultural appropriations from a case study around the album Roots (1996) of the band Sepultura. Using a bibliographical survey, depositions and semi-structured interviews with people directly involved in the production of the disc, besides the analysis of related audio-visual materials, it is verified that the band Sepultura, when claiming an appropriation of indigenous elements and Afro-Brazilian within the genus metal in the analyzed album, establishes a kind of connection between music and the market and creates dichotomous relations that allow us to rethink crystallized categories as “global” and “local”, or the debate about “hybridisms” and “identity” in different cultural contexts.